Penyelenggaraan Peradilan Pidana (Studi tentang: Model-Model dan Faktor-Faktor yang Berperan dalam Peradilan Pidana) - Rusli Muhammad (Jurnal Hukum IUS QUIA IUSTUM, 2002)
The implementation the criminal judicature donotautomatically appear, butit appearsby models support it. Every model applicated and operated in the system of criminal judicature depend on the model selected, but this model is not something concrete but it is something abstract as reflection of the certain values. The implementation the criminal judicature is diseparable with various kinds of factor influence. The harmonious and qualified correlation from these various factors determine very much on the smoothness and the quality of its output. The ignorance for one of the factors would result to the failureand the low of the quality about implementation on the criminal judicature. The various kind of models and factors in implementing the criminal judicature woul be triedto expose on this writing.